Integrating the four language skills trough Task-based Learning with second grade children at Liceo Patria School (2020)
Task-based language teaching (TBLT) is widely used to help students to work through different tasks that are meaningful to them and at the same time, to work on a cooperative way by promoting their communicative language competences. In this study, the use of TBLT through mini projects in each class was proposed with the main aim to develop and integrate all the communicative skills. The purpose of this study was to answer the research question: What is the impact of Task-based Learning and mini-projects on the improvement of the English Language through Integrated Skills in second grade children? This study was applied in a Colombian public school, where 32 students were the participants. The results were collected through a mixed method (qualitative and quantitative research method). The data analysis indicated that students developed their speaking, listening and reading language skills while the writing skill did not show an improvement. However, it is important to say that it was due to spelling mistakes and incorrect grammar structures. In addition, the results indicated that it is a good idea to implement TBLT through mini projects because children can find tasks as motivational. It is important to mention that second grade students showed higher motivation in classes where animals and their classification was presented. Along with this, students also learned greetings, classroom commands and vocabulary because of the routines that were implemented in the classroom. For further researchers it is important to keep in mind that the time allocated for the tasks proposed was highly dependent on the amount of students and the type of task. In that respect, one limitation emerged.